Pengaruh Pembelajaran dan Aksesibilitas terhadap Persepsi Siswa pada Daya Tarik Wisata Pendidikan Kebun Raya Bogor - Suesilowaty, Suesilowaty; Ardhi Nugraha, Rosandi (Attractive : Innovative Education Journal, 2022)
Student's perception toward the Destination Region (DTW) is influenced by various variables. The process of learning received by students and Accessibility; ease to reach DTW is a very important variable to build student perceptions. This research aims to determine the effect of learning and Accessibility to students' perceptions to the Educational Attractions Bogor Botanical Garden. The method used for research is quantitative. The sample of this research consisted of 274 students of SMK in East Jakarta, which were selected by using proportional stratified random sampling technique. The collected data techniques used questionnaires, and data has been analyzed statistically. Based on the overall results of data analysis There was a positive and significant effect between the learning and Accessibility on Student perceptions to the Educational Attractions Bogor Botanical Garden. Keywords: Perception of Student, Influences Learning, Learning Accessibility